Perancangan Smart Door Berbasis ESP32-WROVER dengan Sistem Notifikasi Melalui Aplikasi Blynk - Jardian, Jerry; Kevin; Michael Owen (Telcomatics, 2024)
The advancement of Internet of Things (IoT) technology has significantly transformed traditional home security systems. This research focuses on the design and implementation of a smart door utilizing the ESP32-WROVER microcontroller and Blynk application. The system integrates various components, including a camera (ESP32-CAM), solenoid lock, motion detection sensor, and LCD, to provide a real-time notification and interactive user experience. The smart door enables homeowners to monitor visitors remotely, send custom messages via LCD, and control door locks using their smartphone. Key innovations include the addition of motion sensors for real-time surveillance and enhanced security and the use of LCD to communicate with visitors effectively. The proposed system aims to address limitations in conventional and earlier smart door designs, such as distinguishing between real visitors and objects and providing a comprehensive security solution. The system’s performance was tested using a prototype, demonstrating its ability to improve home security by adjusting and responding to visitor activities effectively. The results show that the smart door provides an integrated ecosystem suitable for modern households, ensuring better safety and convenience. This study, titled “Design of an IoT-Based Smart Door Using ESP32-WROVER with Notification System via Blynk Application”, highlights the application of IoT and automation in creating a more efficient and user-friendly security system.